Stewardship and cancer screening programs in Italy (Italian Journal of Public Health, 2011)
As one of the four major functions of health systems, Stewardship is on the health agenda of several countries worldwide. There is, however, little empirical evidence to support or guide its implementation. To help bridge this gap, the paper aims to contribute to the empirical evidence for health system stewardship and, importantly, to offer implementers an explanatory example of what it could mean in practice. It achieves this by analyzing the experience of the Italian Cancer Screening Programs (from 2004-2009) within a comprehensive framework for health system stewardship. The analysis is largely based on primary and secondary qualitative data, using information collected from an in-depth interview, official documents, and scientific and grey literature. We describe the framework and sub-functions of stewardship, identify the stewardship activities that were carried out by the Programs, and reflect upon the operability of the framework as well as the activities that the Programs have not implemented but would benefit from doing so. The general experience and activities of the Italian Cancer Screening Programs fit well into the stewardship framework, despite not having followed it a priori. Overall, the Programs managed to implement most activities under each sub-function. As an empirical case study, they corroborated the theoretical framework and demonstrated how it could be translated into certain activities on an operational platform. Ultimately, the analysis showed that the framework of stewardship is useful for structuring and prioritizing the most important activities of a steward and, thus, provides a good benchmark for implementers.
Keywords: stewardship; cancer screening; Italy; health systems